A Survey on Aneka Cloud Application and Integration with Windows Azure - Shabana, S; Susmitha, E (International Journal of Computer Sciences and Engineering, 2021)
Aneka is a framework used to implement Platform as a service for cloud computing. Using Aneka features, any complex applications can be easily deployed with benefits either in public or private clouds. Aneka supports all types of cloud providers such as Amazon EC2, Windows Azure and GoGrid. The paper presents how aneka integrates with azure. This integration of both the platforms makes a powerful impact by running more number of compute instances parallel. The advanced features of Aneka platform such as its programming paradigms like programming models, scheduling, Management services, application execution services, accounting and pricing services and dynamic provisioning services. Finally we will determine how aneka works for Amazon EC2 and GoGrid.